The National Narcotics Agency of Kupang City’s Ideal Method for Handling Drug Abuse - Nurdin Nurdin; Ahmad Yusuf Fatah; siti syahida Nurani; Arief Budiono; Satria Akbar (Lembaga Penelitian dan Pengabdian Masyarakat, 2022)
This paper discussed the ideal method for resolving cases of drug abuse by the National Narcotics Agency of Kupang City, East Nusa Tenggara, Indonesia. This study used a sociological juridical approach that is based on the provisions of laws and regulations related to legal theories. It sees the reality that occurs in society, namely the method to resolve the drug abuse issues. The results of the research showed that in handling cases of drug abuse, the National Narcotics Agency of Kupang City carried out the processes of investigation, the transfer of the case to the public prosecutor, and its transfer to the district court. Drug abusers who were red-handedly caught may obtain medical and social rehabilitation based on the judicial decision. It is concluded that the National Narcotics Agency of Kupang City has undergone ideal methods in handling cases of drug abuse.